Alterations to chromatin in intestinal macrophages link IL‐10 deficiency to inappropriate inflammatory responses. Issue 8 (1st June 2016) - Simon, Jeremy M.; Davis, James P.; Lee, Saangyoung E.; Schaner, Matthew R.; Gipson, Gregory R.; Weiser, Matthew; Sartor, R. Balfour; Herfarth, Hans H.; Rahbar, Reza; Sadiq, Timothy S.; Koruda, Mark J.; McGovern, Dermot P.; et al.
Abstract : Unlike macrophages in other tissues, intestinal macrophages are programmed at the chromatin level to be tolerant of intestinal bacteria. IL‐10 deficiency results in intestinal macrophage chromatin alterations that poise them to respond to bacteria with inappropriate inflammation, even in animals raised germ‐free. Abstract : Intestinal macrophages (IMs) are uniquely programmed to tolerate exposure to bacteria without mounting potent inflammatory responses. The cytokine IL‐10 maintains the macrophage anti‐inflammatory response such that loss of IL‐10 results in chronic intestinal inflammation. To investigate how IL‐10‐deficiency alters IM programming and bacterial tolerance, we studied changes in chromatin accessibility in response to bacteria in macrophages from two distinct niches, the intestine and bone‐marrow, from both wild‐type and IL‐10‐deficient ( Il10 −/− ) mice. We identified chromatin accessibility changes associated with bacterial exposure and IL‐10 deficiency in both bone marrow derived macrophages and IMs. Surprisingly, Il10 −/− IMs adopted chromatin and gene expression patterns characteristic of an inflammatory response, even in the absence of bacteria. Further, when recombinant IL‐10 was added to Il10 −/− cells, it could not revert the chromatin landscape to a normal state. Our results demonstrate that IL‐10 deficiency results in stable chromatin alterations in macrophages, even in the absence of bacteria. This supports a model in which IL‐10‐deficiency leads to chromatin alterations that contribute to a loss of IM tolerance to bacteria, which is a primary initiating event in chronic intestinal inflammation.